Chapter 2 Microbial evolution the view from the acidophiles - López de Saro, Francisco J. (De Gruyter, 2015)
In this review we describe the major advances of recent years in the study of the evolutionary mechanisms that shape the genomes of acidophilic organisms, as well as the ecological scenarios in which these changes take place. Finally, we suggest future avenues of research into this fascinating group of microorganisms.